Switching it Up: The Promise of Stimuli‐Responsive Polymer Systems in Biomedical Science - Shymborska, Yana; Budkowski, Andrzej; Raczkowska, Joanna; Donchak, Volodymyr; Melnyk, Yuriy; Vasiichuk, Viktor; Stetsyshyn, Yurij (Chemical record, 2024)
Responsive polymer systems have the ability to change properties or behavior in response to external stimuli. The properties of responsive polymer systems can be fine‐tuned by adjusting the stimuli, enabling tailored responses for specific applications. These systems have applications in drug delivery, biosensors, tissue engineering, and more, as their ability to adapt and respond to dynamic environments leads to improved performance. However, challenges such as synthesis complexity, sensitivity limitations, and manufacturing issues need to be addressed for successful implementation. In our review, we provide a comprehensive summary on stimuli‐responsive polymer systems, delving into the intricacies of their mechanisms and actions. Future developments should focus on precision medicine, multifunctionality, reversibility, bioinspired designs, and integration with advanced technologies, driving the dynamic growth of sensitive polymer systems in biomedical applications. Polymeric stimuli‐responsive systems represent a group of materials that have experienced significant advancements in recent decades. These materials exhibit a physicochemical response based on various factors, such as temperature, pH, light, magnetism, insulin, and others. The promising future of biomedical sciences lies in the rapid and continuous development of these systems.